Cultural Assimilation in the Shifting Trends of Muslim Fashion in Southern Europe - Munthe, Jillena Oseta G; Aminah, Shobicatul; Tairas, David Ronald (Indonesian Journal of Advanced Research, 2026)
The increasing migration of Muslim communities to Europe has significantly influenced fashion trends in the region. One of the most notable changes is the growing demand for Muslim fashion that aligns with modest fashion values. This phenomenon underscores the process of cultural assimilation within the fashion industry, wherein designers and major brands integrate elements of Muslim fashion into their collections. The adoption of modest fashion by global fashion houses not only reflects shifting consumer preferences but also demonstrates the interplay between cultural identity and commercial strategies. This qualitative study adopts a literature review and data analysis approach to examine the consumption and production of Muslim fashion in Southern Europe. The research aims to analyze the extent to which cultural assimilation influences fashion trends, the motivations of fashion brands in incorporating modest fashion, and the socio-economic implications that emerge from this phenomenon. Furthermore, this study seeks to explore the ethical and sustainability concerns surrounding the mass production of modest fashion and its impact on the labor market. A comprehensive understanding of these dynamics is imperative for stakeholders in the fashion industry to develop products that align with evolving consumer preferences while upholding ethical considerations and sustainability principles. By critically assessing the cultural and economic implications of this trend, this study contributes to a broader discourse on globalization, identity, and inclusivity within the fashion industry.